PREPARATION AND CHARACTERIZATION OF DIFFERENT ECO-FRIENDLY DEMULSIFIERS FROM CALABASH SEED FOR EMULSION MANAGEMENT (Nigerian Journal of Technology, 2025)
The process of crude oil demulsification is still confronted with numerous challenges within the petroleum industry. Consequently, it is pertinent to develop innovative means or materials to accomplish the efficient separation of oil–water emulsions. In this work, three different Eco-friendly demulsifier: oil-based, ethanol-based and Nano-based demulsifiers were prepared via a simple one-step hydrothermal route using Lagenaria siceraria (calabash) seed as raw materials. The eco-friendly demulsifiers were evaluated by Fourier transform infrared spectroscopy (FT-IR) and Gas chromatographic-mass spectroscopic (GC-MS) and their chemical content and Physico-chemical properties compared with a commercial demulsifier (Phase treat). The results obtained showed that the seed have an oil content of 31%. The phytochemical screening of the extracted oil reveals the presence of most compounds found in chemical demulsifiers such as phenols, flavonoids, tannins, saponins, steroids, terpenoids etc. The FT-IR spectra of the chemical demulsifier was found to be similar to that of the oil and most of the functional groups present in the ethanol and oil-bases demulsifiers whereas that of Nano-based was observed to differ. The GC-MS analysis reveals the presence of both lipophilic and hydrophilic compound needed for demulsifiers preparation. In the bottle test analysis carried out to determine the efficacy of the eco-friendly demulsifiers, it was observed that the nano-based demulsifier performed better than the commercial demulsifier in the following trend: Nano-based > commercial > ethanol-based > oil-based. This current study not only encourage the effectual application of agricultural waste (Calabash seed), but also creates an understanding   into the search of new demulsifying materials that would offer excellent performance. Finally, future investigations should focus on assessing the efficacy, stability, and potential industrial applications of these bio-demulsifiers and Nano-based demulsifiers.